Cognitive symptoms in early postmenopausal women: Impact on estrogen‐sensitive cholinergic function: Biomarkers (non‐neuroimaging)/Prognostic utility. (7th December 2020) - Newhouse, Paul A.; Conley, Alexander C.; Albert, Kimberly; McDonald, Brenna C.; Saykin, Andrew J.; Dumas, Julie
Abstract: Background: Menopause is associated with increasing cognitive complaints and older women are at increased risk of developing Alzheimer's disease (AD) compared to men. One proposed reason for this reduced cognitive performance is the loss of estrogen following the menopause transition. Estradiol (E2) has been shown to be important for brain cholinergic functioning, the decline of which is linked to AD and cognitive decline. We have previously shown that E2 can attenuate the impact of cholinergic blockade on cognitive performance in normal postmenopausal women. To further explore these relationships, we examined the relationship of menopausal‐associated subjective cognitive complaints (mCC) with E2 effects on cholinergic functioning in postmenopausal women. Method: 56 early postmenopausal women (aged 50‐60 years) with differing levels of mCC completed subjective measures of cognitive complaints and postmenopausal symptoms as well as objective cognitive tests of verbal episodic and working memory and completed a 3‐month treatment regimen of either 1 mg oral 17β‐estradiol or placebo. Participants then completed four cholinergic antagonist drug challenges (mecamylamine, scopolamine, combined mecamylamine+scopolamine, or placebo) and completed cognitive performance tasks including working memory (N‐Back), episodic memory (selective reminding), attention (critical flicker fusion, spatial selective attention), and psychomotor tasks (choice reaction time). Result: All participants performed worse under cholinergic challenge compared to placebo. Higher mCC was associated with greater anticholinergic‐induced impairment on working memory performance and reaction time, but not other measures. E2 treatment did not blunt anticholinergic blockade effects on performance compared to participants who received placebo. On both the CFF and CRT tasks, the performance‐impairing effects of anticholinergic drugs were increased in E2 treated participants compared to placebo treatment. Conclusion: mCC was associated with greater negative effects of anticholinergic drugs on some cognitive domains. In this sample recruited for mCC, E2 treatment did not enhance cholinergic functioning as evidenced by the failure to blunt the effects of cholinergic blockade in contrast to our prior work in normal postmenopausal women. The development of significant menopause‐related cognitive symptoms may represent early brain functional and/or cholinergic changes that may indicate increased risk for cognitive decline and is not modifiable by E2 treatment.